PENERAPAN METODE STUDENT ACTIVE LEARNING (SAL) MELALUI MULTI MEDIA POWER POINT UNTUK MENINGKATKAN KEAKTIFAN, KETERAMPILAN BERDISKUSI, DAN HASIL BELAJAR MATEMATIKA - Rustinah Rustinah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
The purpose of this study is find math learning scenarios format with active student learning method of learning mathematics by using multimedia power point to determine how much influence can enhance the activity, discuss the skills and student learning outcomes. Subjects examined or samples studied were students who study at grade students geometry IX.2 SMP Negeri 3 Batanghari, East Lampung. This study occurred during the three months using three cycles. The variables measured in the study include the involvement of the student in the learning process, skills in using media power point and student learning outcomes. Conclusions of this research is that it can increase the creativity of teachers using a variety of learning resources and selection methods that can encourage the creation of a learning process student active learning with contextual approach through multimedia. Can enhance the activity, and fun atusiasme students during the learning process, improve students' skills in solving problems and improve learning outcomes, especially the material geometry.